“A Tool for Social Change” : Community Photography at Belfast Exposed - Mathilde Bertrand (Revue LISA)
In 1983, an exhibition entitled “Belfast Exposed” opened in Belfast, on an invitation made to local residents and amateur photographers to photographically present their own perspective on the challenges of life in a divided city. The core of photographers involved in the exhibition and its subsequent circulation gave rise to the organisation which took up the name Belfast Exposed. It defined its activities as “community photography”, with direct echoes to similar ventures experimented in mainland Britain in the 1970s. Still in existence today, the organisation has become a highly successful gallery. The article analyses the evolution of community photography practices in the history of this organisation, starting from the premise that community photography first appeared in the 1970s on the back of a very strong rhetoric of empowerment. Over thirty years after its creation, what does community photography at Belfast Exposed mean today, and to what extent does the evolution of the practice reflect the de-politicisation of the concept of empowerment itself ?